Gaps between zeros of solutions for a certain class of third-order differential equations. Issue 1 (2nd January 2019) - Arahet, M. A.; Saker, S. H.; Tunç, Cemil
Abstract: In this paper, we establish some lower bounds for the distance between zeros of nontrivial solutions or/and their derivatives and extend some results about distribution of zeros for a certain class of third-order differential equations of the form M1204 ( r 2 ( t ) ( r 1 ( t ) x ′ ( t ) ) ′ ) ′ + p ( t ) x ′ ( t ) + q ( t ) x ( t ) = 0 . The main results of this paper will be proved by employing some Hardy's and Opial's type inequalities.